Інформаційні технології інтернет-сервісів в освітньому процесі - Нужна, Світлана; Nuzhna, Svitlana; Біловол, Єлизавета; Bilovol, Elizabeth; Петруша, Артем; Petrusha, Artem (Дніпровський державний аграрно-економічний університет, 2020)
Одним з перспективніших завдань на сьогоднішньому етапі модернізації освіти України є забезпечення якості підготовки спеціалістів на рівні міжнародних стандартів. Розв’язання поставленого завдання можливе за умови зміни методик і підходів викладання дисциплін, впровадження інноваційних технологій навчання в освітній процес. One of the most promising tasks at this stage of modernization education of Ukraine is to ensure the quality of training at the level international standards. The solution of the set task is possible under the condition changes in methods and approaches to teaching disciplines, the introduction of innovative learning technologies in the educational process.
Information technologies of Internet services in the educational process
Keywords: модернізація освіти; modernization of education; презентаційні матеріали; presentation materials; хмарний сервіс; cloud service